Repair mechanisms of oxidative DNA damage - Roszkowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2002)
Each aerobic cell during its metabolism produces definite amount of reactive oxygen species (ROS). Aerobic organisms developed defence system that produces antioxidizing enzymes defending the cell from toxic forms of oxygen. Repair systems excising modified nitrogen base and nucleosides from DNA should also be numbered among defence systems. There are two universal paths of repairing DNA impairments caused by ROS: base excision repair (BER) and nucleotide excision repair (NER). The reflection of those two processes in the organism is 8-Oxyguanine and 8-Oxy-2'Deoxyguanosine levels. Nitrogen bases modified by oxidation can be excised from DNA as a result of glycoside bond hydrolysis between damaged base and deoxyribose molecule that causes emerging of apurinic/apyrimidinic (AP) sites in DNA. Bifunctional glycosides apart from the removal of damaged base and formation of AP sites also have lyase properties and remove AP sites by means of b-elimination. In human cells three supplemental ways preventing mutagenic results of 8-Oxyguanine were discovered. The first one is based on removing 8-Oxy-dGTP by specific 8-Oxy-dGTPase, breaking down 8-Oxy-dGTP into 8-Oxy-dGTP that prevents incorporation of that oxygenated nucleoside into DNA by polymerase. 8-Oxy dGTPase of human cells, 18 kDa weight, is called Human Mut Homolog (hMTH1). Disintegration of 8-Oxy-dGTP into 8-Oxy-dGMP precludes repeated incorporation of this nucleotide into DNA. Human 8-oxyguanine glycosylase gen (hOGG1) situated in 3p25 human chromosome codes glycosylase-AP lyase which possesses the ability to excise oxydizing guanine derivative (8-OxyGua) from DNA. Repair process lies in the recognition and excision of modified base by OGG1 protein. Some sources indicate that the gen can be a suppressive one. In yeasts and human cells glycosylase excising 8-OxyGua from 8-OxyGua G and 8-OxyGua A pair was found. The protein is inactive in the presence of 8-OxyGua connected with pyrimidines. It is now called OGG2. The OGG2 removies 8-OxyGua incorporated into DNA during the replication as 8-OxydGTP opposite adenine that prevents AT CG mutations. Cells have supplemental system for glycosylases repairing oxydizing impairments of DNA bases - it means repairing by nucleotides excision (NER). NER is more complicated than BER process and requires ATP as an energy source. DNA damaged fragment is cut from both ends by nuclease and then removed. In case of eukaryotic cells it is the fragment consisting of 27 to 29 nucleotides. Data resulting from in vitro studies on human cells indicate that NER is comprehensive repair mechanism of DNA impairments generated by different carcinogens. In eukaryotic cells DNA lesions caused by photon irradiation are removed according to NER system. BER and NER mechanisms are universal repair systems functioning in both normal cells as well as neoplastic cells subjected to toxic factors such as chemotherapy or radiotherapy.